Psychometric Properties of the Kidney Disease Quality of Life–36 Questionnaire (KDQOL-36™). (August 2016) - Chao, Shumei; Yen, Miaofen; Lin, Tzu-Chia; Sung, Junne-Ming; Wang, Ming-Cheng; Hung, Shih-Yuan
The Kidney Disease Quality of Life–36 Questionnaire (KDQOL-36™), modified by RAND, has been widely used for measurement of quality of life among hemodialysis or peritoneal dialysis patients. The purpose of this study was to refine and evaluate, by using confirmatory factor analysis, the structure of the KDQOL-36™ when the questionnaire was used to evaluate chronic kidney disease patients in Stages 1 to 5 in Taiwan. The psychometric properties of the translated version were determined among Mandarin-speaking adults ( N = 428). Because the sample data did not fit the hypothetical model, one item was deleted and nine error terms were estimated. After improving the model fit, the modified model was presented as follows: χ 2 = 1390.903, χ 2 / df = 2.711, p < .001, goodness-of-fit index = .833, adjusted goodness-of-fit index = .806, root mean square error of approximation = .063. According to the study results, the researchers suggest that because of content overlap, some items may be deducted from the KDQOL-36™.